Go to sleep, Groundhog - Cox, Judy.; Meisel, Paul (New York : Holiday House, 2004)
When Groundhog is unable to sleep, he experiences autumn and winter holidays he never knew about, and then he finally falls asleep before Groundhog Day.
Booklist
3.0
K-3
Keywords: Woodchuck -- Fiction; Groundhog Day -- Fiction; Holidays -- Fiction; Woodchucks -- Fiction; Groundhog Day -- Fiction; Holidays -- Fiction